2006
DOI: 10.1177/0091270005283467
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Aprepitant After Single and Multiple Oral Doses in Healthy Volunteers

Abstract: Aprepitant is the first NK1 receptor antagonist approved for use with corticosteroids and 5HT3 receptor antagonists to prevent chemotherapy-induced nausea and vomiting (CINV). The effective dose to prevent CINV is a 125-mg capsule on day 1 followed by an 80-mg capsule on days 2 and 3. Study 1 evaluated the bioavailability of the capsules and estimated the effect of food. The mean (95% confidence interval [CI]) bioavailabilities of 125-mg and 80-mg final market composition (FMC) capsules, as assessed by simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 13 publications
7
65
0
1
Order By: Relevance
“…earlier studies with various doses of aprepitant indicated some nonlinearity in the disposition of aprepitant, reflecting saturation of metabolism and decreased clearance with an increasing dose. 4,10,18) The low oral bioavailability of aprepitant was also reported to be attributed to its slow dissolution rate, poor permeability across the intestinal mucosa, or first-pass metabolism in the gut and liver. 5) Higher T-Bil was correlated with a higher plasma exposure to aprepitant in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…earlier studies with various doses of aprepitant indicated some nonlinearity in the disposition of aprepitant, reflecting saturation of metabolism and decreased clearance with an increasing dose. 4,10,18) The low oral bioavailability of aprepitant was also reported to be attributed to its slow dissolution rate, poor permeability across the intestinal mucosa, or first-pass metabolism in the gut and liver. 5) Higher T-Bil was correlated with a higher plasma exposure to aprepitant in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4) There are no restrictions in the administration of aprepitant with regard to feeding conditions. 4,5) Aprepitant penetrates the blood-brain barrier and binds to a high degree with brain NK 1 receptors, inhibiting emesis via the central nervous system.…”
Section: Interindividual Variations In Aprepitant Plasma Pharmacokinementioning
confidence: 99%
See 1 more Smart Citation
“…During one study period (i.e., the treatment period), subjects received a supratherapeutic dose of 375 mg of aprepitant after the morning session (T max ϭ 4 h) (Patel and Lindley, 2003;Majumdar et al, 2006), which is known to achieve a level of Ն90% neurokinin-1 receptor occupancy in the central nervous system of humans (Patel and Lindley, 2003;Bergström et al, 2004;Majumdar et al, 2006). During the other period (i.e., control period), no treatment was given.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 249mentioning
confidence: 99%
“…Of note, however, the clinically available NK 1 receptor antagonist aprepitant is administered for the prevention of CINV but not for the treatment of nausea and vomiting, which is possibly due to its relatively slow distribution to the brain. 32,33) Here, we showed the immediate antiemetic activity of the oral administration of FK886 against cisplatin-induced delayed emesis. This is consistent with previous reports of the rapid and efficient distribution of FK886 into the brain in several species other than ferrets.…”
Section: )mentioning
confidence: 77%